The reverse Magnus effect in golf balls - Lyu, B.; Kensrud, J.; Smith, L. (Sports Engineering, 2020)
The following considers the lift and drag response of three commercially available golf balls. The balls were projected with spin through still air in a laboratory setting to investigate a reverse Magnus effect, where balls move in the opposite direction of the expected lift force. The drag and lift coefficients were found by measuring ball position and speed at three points along its trajectory. Three ball types, with different dimple patterns, exhibited reverse Magnus behavior between 5 × 10^4 < Re < 7 × 10^4 and 750 < w < 2250 rpm. The golf ball with circular dimples had the least severe reverse Magnus effect, CL = - 0.1, while the ball with hexagonal dimples had the greatest, CL = - 0.15. The magnitude of the reverse Magnus effect was related to the drag crisis of each ball model. As the slope of the drag crisis became steeper, the magnitude of the reverse Magnus effect increased.